ABOUT TAXATION: TAX INCENTIVES VS TAX AMNESTY - Cîrmaciu, Diana (International Journal of Legal and Social Order, 2024)
In the current period, the question arises of the appropriateness of the fiscal amnesty approved by the governors. To be able to answer, we consider it useful to understand the legal framework of this mechanism, its advantages and disadvantages, the risks it could induce. We will also analyze, by comparison, the concept of tax incentives, drawing the differences between the two notions. However, we must remember that both measures are decided by the governors in order to support taxpayers, differentiating themselves through their own application mechanisms.